Tumor-specific CD8 T cell characterization in HR+ breast cancer reveals an impaired antitumoral response in patients with lymph node metastasis - Pinho, Mariana Pereira; Antoun, Elie; Sandhar, Balraj; Shu, Ting; Gao, Fei; Yang, Xiaobao; Bates, Adam; Cerundolo, Lucia; Hamid, Megat H.B.A.; Maldonado-Perez, David; Teague, Renuka; Warner, Eve; et al. (Cell reports. Medicine, 2025)
Most breast cancers express the estrogen receptor (ER), but the immune response of hormone receptor-positive (HR+) breast cancer remains poorly characterized. Here, dendritic cells loaded with tumor lysate are used to identify tumor-reactive CD8 T cells, which are detected in most HR+ breast cancer patients, especially those with early-stage tumors. When present, the circulating antitumor CD8 response contains cytotoxic T cells with diverse specificity and T cell receptor (TCR) repertoire. Additionally, patients with blood cancer-specific T cells have significantly more CD8 tumor-infiltrating lymphocytes (TILs). Moreover, tumor-reactive TCR sequences are detected in the tumor, but at a significantly lower proportion in patients with lymph node involvement. Our data suggest that HR+ breast cancer patients with lymph node metastasis lack tumor-specific CD8 T cells with capacity to infiltrate the tumor at significant levels. However, early-stage patients have a diverse antitumor CD8 response that could be harnessed to develop immunotherapeutic approaches for late-stage HR+ patients. [Display omitted] •Antitumor CD8 T cells are detected in patients with early-stage breast cancer•When present, the tumor-reactive blood CD8 T cell repertoire is highly diverse•Presence of circulating tumor-reactive T cells correlates with CD8 TIL abundance•Patients with lymph node metastasis have lower frequency of tumor-reactive TILs Pinho et al. show that HR+ breast cancer patients with lymph node metastasis have an impaired antitumor CD8 immune response, with less frequency of tumor-reactive TILs. Yet, early-stage patients exhibit a diverse tumor-reactive CD8 T cell repertoire that could be harnessed to develop immunotherapeutic interventions for late-stage HR+ patients.